The Use of Surgical Apgar Score as a Predictor of Postoperative ICU Admission - Nugroho, Stefanus Danan; Jufan, Akhmad Yun; Fajar Apsari, Ratih Kumala (Jurnal Komplikasi Anestesi, 2025)
Background: Postoperative Intensive Care Unit (ICU) care can improve outcomes in high-risk surgical patients. The Surgical Apgar Score (SAS) was developed to predict postoperative morbidity and mortality; however, its ability to predict ICU admission remains unclearObjective: To evaluate the utility of the SAS as a predictor of postoperative ICU admission.Methods: This prospective cohort study included 314 surgical patients at Dr. Sardjito General Hospital between June and July 2025. Data on demographics, preoperative status, intraoperative variables (including the SAS), ICU admission, and postoperative mortality were analyzed using both bivariate and multivariate methods.Results: Lower SAS scores were significantly associated with an increased risk of postoperative ICU admission in multivariate analysis, particularly in SAS categories 0–2 (OR 326.45; p = 0.016) and 5–6 (OR 47.39; p = 0.037). The ROC curve of SAS for predicting postoperative ICU admission yielded an AUC of 0.701 (p = 0.001; 95% CI: 0.62–0.78) with a cut-off value of 6.5. Neurosurgical and vascular thoracic procedures, cardiovascular comorbidities, intraoperative vasopressor use, and surgical duration greater than 2 hours were also strong predictors of postoperative ICU admission. The postoperative mortality rate was 3.5%, mainly associated with surgical duration exceeding 6 hours (predictive factor) and other types of surgery (protective factor). The SAS, with clinical factors such as procedure type, comorbidities, and surgical duration, may help guide the decision for postoperative ICU admissionConclusion: The SAS is a useful tool for predicting postoperative ICU requirements.